First Report on the Synthesis of Antipyrine Crowned Siloxy Framework: Optical Recognition of Fe2+ and Hg2+ Ions. Issue 28 (30th July 2020) - Singh, Gurjaspreet; Satija, Pinky; Singh, Akshpreet; Sushma,; Sharma, Geetika; Mohit,; Pawan,; Suman,; Priyanka,
Abstract: The present work explores the synthesis and characterization of antipyrine crowned Organosilatranes from a condensation reaction between antipyrine and amino silane followed by transesterification reaction with tripodal ligand. A highly selective chemosensor based on the prepared antipyrine crowned Organosilatrane exhibited remarkable selectivity and sensitivity towards Fe 2+ and Hg 2+ ions. The sensor binds to these ions at 1 : 1 stoichiometry and with high affinity as determined by Jobs plot and apparent from binding constant values of 4.05 ×10 5  M −1 and 3.79 ×10 5  M −1 respectively. The structure of newly synthesized silanes and Organosilatranes were corroborated by numerous spectroscopic techniques. Abstract : The current study involves synthesis and characterization of antipyrine crowned Organosilantranes by employing condensation route and transesterification reaction for the selective and sensitive detection of Fe 2+ and Hg 2+ ions. The sensor binds with high affinity to these ions at 1 : 1 stoichiometry as determined by Jobs plot and apparent from the binding constant values of 4.05 ×10 5  M −1 and 3.79 ×10 5  M −1 respectively.